Training organization, physiological profile and heart rate variability changes in an open-water world champion - Pla, R.; Aubry, A.; Resseguier, N.; Merino, M.; Toussaint, J.-F.; Hellard, P. (International Journal of Sports Medicine, 2019)
This case study reports the training of an elite 25-km open-water swimmer and the daily heart rate variability (HRV) changes during the 19-week period leading to his world champion title. Training load was collected every day and resting HRV was recorded every morning. The swimmer`s characteristics were VO2max: 58.5 ml·min-1·kg-1, maximal heart rate: 178 beats per minute, and maximal ventilation: 170 L·min-1. Weekly training volume was 85±21 km, 39±8% was at [La]b<2 mmol · L-1 (Z1), 53±8% was at [La]b 2-4 mmol·L-1 (Z2), and 8±4% was at [La]b>4 mmol·L-1 (Z3). In the supine position, the increase in training volume and Z2 training were related to increases in rMSSD and HF. In the standing position, an increase in parasympathetic activity and decrease in sympathetic activity were observed when Z1 training increased. Seasonal changes indicated higher values in the LF/HF ratio during taper, whereas higher values in parasympathetic indices were observed in heavy workload periods. This study reports extreme load of an elite ultra-endurance swimmer. Improvements in parasympathetic indices with increasing Z2 volume indicate that this training zone was useful to improve cardiac autonomic activity, whereas Z1 training reduced sympathetic activity.